Control of buck boost converter with Mamdani Fuzzy inference system using Microcontroller Arduino - Syafyutina, Rahmat Alwafi; Yuhendri, Muldi; Dewi, Citra; Hendra, Ayu (Journal of Industrial Automation and Electrical Engineering, 2024)
Various electrical equipment utilizes direct voltage (DC) as a power source. Examples of this equipment include various electronic devices as well as DC motors and others. The direct voltage used usually has various ratings, ranging from 1.5 volts to 12 volts, and other numbers. To ensure that the direct voltage is in accordance with the tool's needs, it is necessary to control this voltage. This control is generally carried out using a power converter. In this research, buck-boost converter output voltage control will be implemented using the Fuzzy Mamdani method with an Arduino Atmega 2560. The control system developed will be tested through experiments in the input voltage range between 12 to 24 Volts, with a maximum output of 18 Volts. The experimental results show that the Fuzzy Mamdani based buck-boost converter output voltage control system successfully regulates the output voltage according to the desired reference value